LUX INCORPORATA. The Theme of Light and Its Ancient Sources in the Imagery of Christian Art - Mihail M. Gheațău (Anastasis: Research in Medieval Culture and Art)
This study attempts to identify the theme of light in the imagery of ancient Greco-Roman and Christian art through a comparative analysis of the context and evolution of artistic language before and after the Christianization of the Roman Empire. An essential criterion in understanding the new aesthetic paradigm and highlighting the means of artistic expression characteristic to the two periods temporally delimited by the event of the Incarnation, is the way in which artistic consciousness relates to divinity. The acceptance or not of the Revelation, the reflection in religious art of the fact that God became Man and He has a Face, as opposed to other philosophical quests and religious systems that dress up the idea of divinity and its attributes in the face of the gods, personifying it or imagining it symbolically, – makes the difference. God communicates Himself to man through light, light being the common denominator of any epistemology, without placing in competition or in opposition the knowledge that comes to us through Revelation with that acquired by man through scientific experiments. Paradox is a mark of light. Science has proven it with the wave-particle dualism of quantum mechanics and theology fully confirms it. Light is a Person who says of Himself that He is: ‘The Light of the World’. (John 8, 12). The theme of light has multiple meanings in biblical exegesis; from the metaphorical image that runs through the Book of Revelation to that of the incorporated Light (Lux incorporata), an interpretation that refers to the Mystery of the Incarnation, to the world transfigured by grace, to the uncreated light communicated to people by the heavenly hierarchies through the Church in the form of the Holy Mysteries. In the world of late Roman antiquity, and later in the Byzantine world, there was a belief that the veining or luminous veins of colored marble, gemstones or translucent stones were embedded rays of light, an intervention of divine light in the rock. The uniqueness of these ‘graphic accidents’ was interpreted as signs of God in the creation that suggests the unseen, the unusual, the ineffable, in short, the paradox of the Christian world summed up in this confession: that God is both One and Three, that Christ is both Man and God, and that Mary is both the Mother of God and the Virgin. The art of mosaics and stained glass, as well as the entire decorative complex of precious stones, gems and polychrome marbles adorning objects of worship and liturgical furnishings, is built on a long tradition that aesthetically and theologically values the motif of light. Dogmatic notions such as hypostatic union and perichoresis are symbolically translated into visually striking plastic expressions – provided by the natural textures of the cut and polished rocks – with the sole purpose of suggesting the dogmatic ‘contradictions’ of the Kingdom of Light which, as they say, ‘already exists, but not yet’.